2016
DOI: 10.1038/srep34773
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen separation through tailored dual phase membranes with nominal composition BaCe0.8Eu0.2O3-δ:Ce0.8Y0.2O2-δ at intermediate temperatures

Abstract: Hydrogen permeation membranes are a key element in improving the energy conversion efficiency and decreasing the greenhouse gas emissions from energy generation. The scientific community faces the challenge of identifying and optimizing stable and effective ceramic materials for H2 separation membranes at elevated temperature (400–800 °C) for industrial separations and intensified catalytic reactors. As such, composite materials with nominal composition BaCe0.8Eu0.2O3-δ:Ce0.8Y0.2O2-δ revealed unprecedented H2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…In mice HZE irradiation was about 3 times more effective compared to gamma-rays for induction of an acute neuroinflammatory response, and increased expression of the CCR2 receptor was observed in the subgranular zone 9 months after 1–3 Gy 12 C or 56 Fe irradiation (Rola et al, 2005). In vitro studies have shown that HZE particles produce significantly higher levels of ROS compared to low LET radiation (Limoli et al 2007), and a persistent inflammatory response at lower doses for post-irradiation times of 1-month or more (Parihar et al 2016, Cherry et al 2013). However it is not clear if a significant induction of neuroinflammation occurs in the hippocampus at lower HZE particle doses (0.1 to 0.5 Gy) within the first 30 d post-irradiation (Rola et al, 2008) with less known for other brain regions.…”
Section: Mechanisms Of Radiation Induced Cognitive Detrimentsmentioning
confidence: 99%
“…In mice HZE irradiation was about 3 times more effective compared to gamma-rays for induction of an acute neuroinflammatory response, and increased expression of the CCR2 receptor was observed in the subgranular zone 9 months after 1–3 Gy 12 C or 56 Fe irradiation (Rola et al, 2005). In vitro studies have shown that HZE particles produce significantly higher levels of ROS compared to low LET radiation (Limoli et al 2007), and a persistent inflammatory response at lower doses for post-irradiation times of 1-month or more (Parihar et al 2016, Cherry et al 2013). However it is not clear if a significant induction of neuroinflammation occurs in the hippocampus at lower HZE particle doses (0.1 to 0.5 Gy) within the first 30 d post-irradiation (Rola et al, 2008) with less known for other brain regions.…”
Section: Mechanisms Of Radiation Induced Cognitive Detrimentsmentioning
confidence: 99%
“…This advanced casting technique involves the inversion of the traditional tape casting approach’s necessary manufacturing steps and produces homogeneous, large-area, flat ceramic films. This method has been used for the fabrication of solid oxide-oxygen ions conducting fuel and electrolysis cell (O-SOFC/O-SOEC) [ 21 , 23 ] as well as hydrogen [ 31 , 32 ] and oxygen separation membranes [ 33 , 34 , 35 ]. Another great advantage of this technique is its potential to minimize manufacturing cost since multi-layer components are laminated and co-sintered in a single step [ 23 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single phase MPECs can have good stability but prohibitively low H 2 permeation fluxes. However, when a second electrically conducting phase is added, H 2 permeation values can be much higher [3][4][5][6] . BaCe 0.8 Y 0.2 O 3-δ -Ce 0.8 Y 0.2 O 2-δ (BCY-YDC) in which the BCY phase is the primary proton conductor and the YDC phase is the electronically active phase, 7 has shown promising H 2 permeation results 4 and is the focus of the current work.…”
Section: Introductionmentioning
confidence: 99%